Análise da diversificação no mercado de mineração - Valente, Bruno Kauffmann Gurgel (2017)
During the period known as the commodities super cycle (2000 – 2011) the mining market saw its main companies adopting a diversification strategy from its core business, acquiring existing companies or entering in greenfield projects in various markets. 6 years after this period and going through a market environment with commodities prices under pressure due to the decrease of the global demand, this study seeks to analyze if the diversification strategy by these companies achieved the objective of increasing the company value. By analyzing a complete cycle, high and low, the empirical evidence leads us to conclude that as companies that remained focused on their core businesses were more benefited in the long run in relation to their market value than those that have diversified.